(3GdEadGSs - (3GdjGS(B, (3CHh GdYjOs ((3HjQhJ(B:s [(3O(B.(3f(B.],s, 1998)
(3JWHjb bhGfjf GdGadGS ef MjK GdReGf, TgQ GdGadGS, GdTQhW GdehVhYjI dTgQ GdGadGS, JhaQ UaI GdJGLQ(B: (3JLGQ GdCaQGO GdTQcGJ, GdJhba Yf GdOaY(B: (3JYQjag hJejRg Yf YOe GdedGAI Ch GdGYSGQ hGdVGFYI GdeGdjI GdeDbJI, TQhW JMbb MGdI GdJhba Yf GdOaY dOi GdJLGQ GdCaQGO, Jhba GdeUGQa Yf GdOaY, GKHGK GdJhba Yf GdOaY, GdGadGS HYO GYJRGd GdJLGQI, GdGadGS HYO GdhaGIs
Keywords: (3GdEadGSs